KONTAMINASI TELUR CACING NEMATODA USUS PADA SAYURAN YANG DIJUAL DI PASAR BESAR PALANGKA RAYA - FEBRI NUR NGAZIZAH; Fandi Tuju; Martini Tresia Tampubolon; Niken Tri Handayani (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Vegetables are an important food source because they contain vitamins and minerals. However, vegetables that are contaminated with intestinal nematode eggs and then consumed raw or not washed and cooked properly can become a medium for transmitting intestinal nematode eggs and cause worms. Worms are included in the category of neglected tropical diseases (Neglected Tropical Diseases) where this disease receives little attention and treatment, even though it can cause serious health problems, especially in children, it can cause growth disorders. The purpose of this study was to determine the presence of intestinal nematode eggs in various types of vegetables, namely basil (Ocimum sanctum), kale (Ipomoea aquatica), spinach (Amaranthus tricolor) and lettuce (Lactuca sativa) sold in traditional markets in Palangka Raya as an effort to ensure food safety and control parasitic diseases. The study used a descriptive survey method by conducting microscopic examinations in the laboratory, examination of worm eggs was carried out using the flotation method using 0.9% NaCl. The total number of vegetable samples was 20 samples. The results showed that vegetable samples were contaminated with intestinal nematode eggs with a percentage of positive vegetable samples contaminated with intestinal nematode eggs of 8 samples (40%) and negative samples of 12 (60%). The species of intestinal nematodes that contaminate are Ascaris lumbricoides, Trichuris trichiura and Enterobius vermicularis. The results of this study can add information to always maintain food hygiene, especially vegetables that will be consumed